2001
DOI: 10.2337/diacare.24.9.1653
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between ACE Gene and ecNOS Gene Polymorphisms and Resistive Index in Type 2 Diabetic Patients With Nephropathy

Abstract: OBJECTIVE -ACE and endothelial cell nitric oxide synthase (ecNOS) genotypes have been reported to be related to the incidence of renal diseases and coronary artery diseases. In order to assess the effect of the gene polymorphism of both ACE and ecNOS on renal hemodynamic abnormality, we examined 155 Japanese patients with type 2 diabetes with various stages of nephropathy.RESEARCH DESIGN AND METHODS -The patients ranged in age from 40 to 72 years (92 men and 63 women). They were divided into four groups: group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 30 publications
2
26
0
1
Order By: Relevance
“…Three polymorphisms in this gene G894T missense mutation (rs1799983), a 27-bp repeat in intron 4, and the T786C single nucleotide polymorphism (SNP) in the promoter (rs2070744) have been found to be associated with diabetic nephropathy susceptibility [26][27][28][29][30] . The G894T variant was found to increase the risk of macroalbuminuria and progression from microalbuminuria to macroalbuminuria, with declining glomerular filtration rate as serum creatinine value rises progressively, culminating in nephropathy [31,32] However, these results have been contradictory and not all studies support this association [33][34][35] . Recent studies on different gene variants observed that there was an association between eNOS4b/a polymorphism and the risk of type 2 diabetic nephropathy [36,37] while others suggested that there was no significant association [38] .…”
Section: Gene Variants Of Renal Function Componentsmentioning
confidence: 75%
“…Three polymorphisms in this gene G894T missense mutation (rs1799983), a 27-bp repeat in intron 4, and the T786C single nucleotide polymorphism (SNP) in the promoter (rs2070744) have been found to be associated with diabetic nephropathy susceptibility [26][27][28][29][30] . The G894T variant was found to increase the risk of macroalbuminuria and progression from microalbuminuria to macroalbuminuria, with declining glomerular filtration rate as serum creatinine value rises progressively, culminating in nephropathy [31,32] However, these results have been contradictory and not all studies support this association [33][34][35] . Recent studies on different gene variants observed that there was an association between eNOS4b/a polymorphism and the risk of type 2 diabetic nephropathy [36,37] while others suggested that there was no significant association [38] .…”
Section: Gene Variants Of Renal Function Componentsmentioning
confidence: 75%
“…A recent meta-analysis of published studies reported evidence of linkage for fasting glucose and insulin resistance to 7q36, the genomic region to which the eNOS gene maps (33). Although large population-based cohort studies examining the relationship between variation at the eNOS gene and glucose intolerance are scarce (34), several clinical studies in people with type 2 diabetes have examined the association of eNOS polymorphisms with hypertension (35), nephropathy (36,37), retinopathy (38), and ischemic heart disease (39).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies 1 investigated 3 polymorphisms together: G894T, 4a/b, and T786C. The design in 24 studies was case-control,* in 7 studies was population-based cohort, 4,29,31,36,43,45 and in 4 studies was cross-sectional. 23,37,34,47 The studies were published between 1995 and 2006.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…23,24,29,32,51,52 The polymorphism 4a/b was genotyped using electrophoretic differentiation. 1,25,27,28,35,36,[41][42][43][44][45][46][47][48][49] Five studies stated that the controls were age or sex matched. 29,30,38,48,53 24,33 provided data for males and females separately.…”
mentioning
confidence: 99%